Improvement in coronary haemodynamics after percutaneous coronary intervention: assessment using instantaneous wave-free ratio. Issue 23 (18th September 2013) - Nijjer, Sukhjinder S; Sen, Sayan; Petraco, Ricardo; Sachdeva, Rajesh; Cuculi, Florim; Escaned, Javier; Broyd, Christopher; Foin, Nicolas; Hadjiloizou, Nearchos; Foale, Rodney A; Malik, Iqbal; Mikhail, Ghada W; et al.
Abstract : Objective: To determine whether the instantaneous wave-free ratio (iFR) can detect improvement in stenosis significance after percutaneous coronary intervention (PCI) and compare this with fractional flow reserve (FFR) and whole cycle Pd/Pa. Design: A prospective observational study was undertaken in elective patients scheduled for PCI with FFR ≤0.80. Intracoronary pressures were measured at rest and during adenosine-mediated vasodilatation, before and after PCI. iFR, Pd/Pa and FFR values were calculated using the validated fully automated algorithms. Setting: Coronary catheter laboratories in two UK centres and one in the USA. Patients: 120 coronary stenoses in 112 patients were assessed. The mean age was 63±10 years, while 84% were male; 39% smokers; 33% with diabetes. Mean diameter stenosis was 68±16% by quantitative coronary angiography. Results: Pre-PCI, mean FFR was 0.66±0.14, mean iFR was 0.75±0.21 and mean Pd/Pa 0.83±0.16. PCI increased all indices significantly (FFR 0.89±0.07, p<0.001; iFR 0.94±0.05, p<0.001; Pd/Pa 0.96±0.04, p<0.001). The change in iFR after intervention (0.20±0.21) was similar to ΔFFR 0.22±0.15 (p=0.25). ΔFFR and ΔiFR were significantly larger than resting ΔPd/Pa (0.13±0.16, both p<0.001). Similar incremental changes occurred in patients with a higher prevalence of risk factors for microcirculatory disease such as diabetes and hypertension. Conclusions: iFR and FFR detect the changes in coronary haemodynamics elicited by PCI. FFR and iFR have a significantly larger dynamic range than resting Pd/Pa. iFR might be used to objectively document improvement in coronary haemodynamics following PCI in a similar manner to FFR.